2015
DOI: 10.14791/btrt.2015.3.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Gamma Knife Radiosurgery for Intracranial Meningioma

Abstract: BackgroundThe predominant treatment modality for meningioma is surgical resection. However, gamma knife radiosurgery is also an important treatment modality for meningioma that is small or cannot be completely removed because of its location. In this study, we evaluated the effectiveness and long-term results of radiosurgical treatment for meningioma in our institution.MethodsWe studied 628 patients (130 men and 498 women) who underwent gamma knife radiosurgery for intracranial meningioma, which is radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…The large study from the Hospital Na Homolce in Prague published by Kollova and colleagues had demonstrated peri-lesional oedema after radiosurgery in 15.4% and temporary and permanent morbidity rates of 10.2% and 5.7%, respectively [28]. Virtually the same rate for the risk of oedema (15%) was recently reported in large series by Jang (15%) [23] or by Hoe (15.3%) [18].…”
Section: Adverse Radiation Effectsmentioning
confidence: 64%
See 2 more Smart Citations
“…The large study from the Hospital Na Homolce in Prague published by Kollova and colleagues had demonstrated peri-lesional oedema after radiosurgery in 15.4% and temporary and permanent morbidity rates of 10.2% and 5.7%, respectively [28]. Virtually the same rate for the risk of oedema (15%) was recently reported in large series by Jang (15%) [23] or by Hoe (15.3%) [18].…”
Section: Adverse Radiation Effectsmentioning
confidence: 64%
“…The Gamma Knife was the first available technology for stereotactic neuro-radiosurgery [ 12 ] with its 3D precision for the delivery of radiation still being unsurpassed. Gamma Knife radiosurgery (GKRS) of meningioma is highly effective with 5-year actuarial tumour control rates (or 5-year actuarial progression-free survival) ranging between 87 and 98.5% in 36 Gamma Knife radiosurgery (GKRS) of meningioma is highly effective with tumour control rates ranging between 70 and 98.5% in 39 Gamma Knife series comprising a total of 12,431 patients published between 2000 and December 2018 [ 2 , 4 , 5 , 7 , 9 11 , 13 , 14 , 16 21 , 23 , 25 , 26 , 28 , 30 , 31 , 34 36 , 38 , 44 46 , 48 , 49 , 51 , 52 , 54 , 56 59 , 61 ] (Table 1 ). Since meningiomas are slowly growing tumours, it is paramount to validate these results in a long-term perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the predictors of tumor recurrence or progression, some studies revealed that increasing tumor volume was an independent predictor, which was also proved in our study. 10,16,29 In this study, many patients with intracranial meningiomas had low subjective acceptance of craniotomy; even though there were significant mass effect or neurological symptoms or signs, they preferred GKRS instead of craniotomy, which resulted in a high rate of large tumor (≥ 10 cm 3 ) in proportion at the time of GKRS, and reduced the treatment effect of GKRS in the cohort. In addition, a GKRS dose-plan defect may also influence local tumor control.…”
Section: Discussionmentioning
confidence: 77%
“…Otherwise, rates of local control for grade II meningioma range from 41.7% to 95% following photon-based SRS. 8,14,34 Survival rates are especially poor for grade III meningioma treated with photon therapy, ranging from 40% to 44% at 5 years. 49,66 Local control (72%-82.6%) and freedom from recurrence have been favorable but variable for atypical meningioma treated with any form of radiation therapy.…”
Section: Prognostic Factors For Local Tumor Control and Overall Survivalmentioning
confidence: 99%